Efficiency Wages and Labor Mobility in an Open Economy - Santaella, Julio; Agenor, Pierre-Richard. (Washington, D.C. : International Monetary Fund, 1993)
The paper analyzes the role of labor market segmentation and relative wage rigidity in the transmission process of macroeconomic shocks in a two-sector optimizing model of a small open economy. The analysis is first conducted in the context of perfect intersectoral labor mobility. The discussion is then extended to consider the existence of short-run constraints on labor movements. The results highlight the role of efficiency considerations in the behavior of sectoral wages. A deflationary policy induces a reallocation of labor across sectors, but has no long-run effect on the unemployment rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet